Attitudes of Science and Social Studies Department Students in Urban and Village High School in Papua Province Concerning HIV/AIDS - Juniasti, Helen Try; Asriati, Asriati; Weya, Arinus (Devotion : Journal of Research and Community Service, 2023)
The knowledge of students in cities and villages about HIV is higher in the low category at 55.2%, then in the medium category at 24.7%, and in the high category at 20.1%, students in cities are most in the medium level of knowledge category while students in villages are most in the high level of knowledge category. The attitude of students in cities and villages has a positive attitude category about HIV prevention. The purpose of this study is to determine the comparison of attitudes of students majoring in science and social studies about reproductive health and HIV in urban and rural high schools in Papua Province.  This study used quantitative method with a cross-sectional research design to identification the differences in attitudes between students majoring in science and high school social studies in cities and villagesFrom this study give some implication such as identified the differences in attitude of students majoring in science and social studies.  The result of this study shows that the level of Science students have a more positive attitude towards HIV prevention than social studies students in high schools in cities and villages.